RAISING INTEREST IN MALAY CLASSIC LITERATURE IN YOUNG READERS - Ding Choo Ming (Jurnal Elektronik WACANA ETNIK, 2015)
The interest in reading printed books has tapered off in this digital age as shownby reports of continual loss from many book publishers over the years. What todo to whet reading habits, especially among the young? What are the optionsin store in book publishing? What can publishing experts predict? What can wesay how to whet reading habit? We know that without reader, more publisherswill wind up their business. Thus, new ways and outlets have to search.Though Malay hikayat are considered important, they are not interesting. Tomake them interesting, relevant and acceptable to young readers, publishersmust recognize the twin purposes of instruction and delight that have longbeen accepted as the primary goals of books for children and the fact that theyare important and form a distinctive category of readers with separate needsand interests. Only by making the books interesting, relevant and acceptableto them, Malay hikayat can hope to live on. Though physically weak, they arespiritually, emotionally and imaginatively strong. Stories about animals, fantasyand legends are popular with them. They love the illustrated books, cartoons,comics, movies and others on Pak Pandir, Pak Belalang, Singapura DilanggarTodak, Puteri Gunung Ledang, Hang Tuah dan Hang Jebat. These stories arealso among the  nest examples of moral tales that encourage them to focus onself-improvement like Aesop fables, stories from Grimn’s brothers. This meansthat integration of visual and verbal elements has remained a signi cant featureto attract children. In this paper, we argue that publishers must adapt storiesfrom Malay classical literature to illustrated books, movies, comics, movies,  lmsand e-books. Linking the best visual and verbal elements in these publicationsis the way forward to teach literacy, history and moral to young readers.